Chronic malaria and hyper-reactive malarial splenomegaly: a retrospective study on the largest series observed in a non-endemic country. (December 2016) - Bisoffi, Zeno; Leoni, Stefania; Angheben, Andrea; Beltrame, Anna; Eseme, Franklyn; Gobbi, Federico; Lodesani, Claudia; Marocco, Stefania; Buonfrate, Dora
Abstract Background Chronic malaria is usually defined as a long-term malarial infection in semi-immune subjects, usually without fever or other acute symptoms. The untreated infection may evolve to hyper-reactive malarial splenomegaly (HMS), a life-threatening complication. This paper describes the largest series of HMS ever observed outside endemic countries, and the clinical outcome after a single anti-malarial treatment. Contrarily to most authors, still reporting the traditional, long-term treatment, regardless possible further exposure, the patients in this series did not receive any further prophylaxis if they were not re-exposed to malaria infection. Methods A retrospective, longitudinal study, describing all patients with HMS diagnosed at the Centre for Tropical Diseases of Negrar, Verona, took place over a 25-year period. HMS was defined by a longitudinal spleen diameter ≥16 cm, IgM ≥ 2.5 g/L, anti-malarial antibody titre ≥160, exclusion of other causes of splenomegaly. The short-term (≤6 months) clinical outcome after a single anti-malarial treatment was analysed and so was the long-term outcome of subjects re-exposed to malaria and submitted or not to anti-malarial prophylaxis or intermittent treatment. The association of the outcome with the main independent variables was first assessed with univariate analysis. Logistic regression was also performed. Results Forty-four subjects with HMS were retrieved. Of those with a short-term follow-up visit (<6 months, median 43 days) available before returning to endemic areas, 20/22 resulted improved/cured, two were unchanged. Of 22 expatriates seen at long-term follow-up after re-exposure, 18 were improved/cured, including eight out of nine who had followed an anti-malarial prophylaxis and 10/13 who had opted for the alternative of an intermittent treatment. Conclusion HMS is the most severe form of chronic malaria. A single anti-malarial treatment is probably adequate to treat HMS in the absence of re-exposure, while an adequate prophylaxis is necessary for patients exposed again to malaria transmission. Intermittent treatment would probably be the only viable approach in endemic countries.